The Effect Of Sensory-Motor Virtual Reality on Balance in Children with Clinical Down Syndrome - Fanny Thresia Yunus; I Made Widagda; Rahmi Isma (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Introduction: Down syndrome affects approximately one in every 800 live births and leads to musculoskeletal disorders and motor skill delays. Children with down syndrome experience persistent deficits in balance and coordination. Virtual reality (VR) offers an interactive and immersive approach to therapy and has gained popularity in rehabilitation. This study explores the effect of sensory-motor virtual reality (VR SenMor) on static and dynamic balance in children with clinical down syndrome. Methods: A randomized controlled trial with a pre and post-test control group design was conducted with 20 children diagnosed with down syndrome. Treatment group (n = 10) received VR SenMor therapy twice a week for four weeks, while the control group (n = 10) received no treatment. Balance assessments were conducted using the pediatric balance scale (PBS) and timed up and go (TUG) test before and after the intervention. Results: There were no significant differences in age, gender, or BMI between the intervention and control groups. The VR SenMor therapy resulted in significant improvements in the PBS and TUG test scores in the intervention group compared to the control group. Discussion: VR SenMor therapy enhanced balance in children with down syndrome, with no confounding effects from age and gender. The VR system's sensory integration feedback and neuroplasticity mechanisms contributed to the improvements. The treatment's positive outcomes make it a promising approach for balance training at home. Conclusion: Sensory-motor virtual reality therapy shows promise in enhancing static and dynamic balance in children with clinical down syndrome.